A concept analysis of obstetric violence in the United States of America. Issue 4 (7th July 2020) - Garcia, Lorraine M.
Abstract: The aim is to clarify the concept of "obstetric violence in the United States of America." Obstetric violence (OV) is a poorly defined and rarely applied concept in the United States that causes significant harm and requires recognition. The design is a concept analysis to examine the structure and function of OV in the United States. An English language literature review with no date restrictions was performed using CINAHL, PubMed, and Google search. The search was expanded to the related terms "birth rape" and "birth trauma." The concept analysis was conducted using the method outlined by Walker and Avant. The synthesized definition proposed is: Obstetric violence is abuse or mistreatment by a health care provider of a female who is engaged in fertility treatment, preconception care, pregnant, birthing, or postpartum; or the performance of any invasive or surgical procedure during the full span of the childbearing continuum without informed consent, that is coerced, or in violation of refusal. It is a sex‐specific form of violence against women (VAW) that is a violation of human rights. A clear definition and understanding of OV in the United States will allow for its recognition. A conceptual basis for naming it can lead to better knowing its prevalence, further studies, and operationalizing the term to create pathways for accountability and restitution. Nurses are in a unique position to minimize OV risk and to promote individual and unit‐based responses for zero‐tolerance.